How Does Psychological Contract Mediate the Effect of Transformational Leadership on Job Satisfaction? Moderating Variable of Tenure - Muhajiroh, Nailatul; Noermijati, Noermijati (UIN Sunan Gunung Djati, 2024)
This research investigates how the role of the mediating variable of psychological contract and the moderating variable of tenure on the influence of the independent variable of transformational leadership on job satisfaction in Indonesian government organizations. This research is in line with Decker, (2018) the results of the study show that transformational leadership significantly affects job satisfaction, this is also expressed in research. Masal, (2015) with the title